Moderation and Mediation of Meaningful Work on Job Demands and Job Resources on Work Engagement - Aria Srihadiningrat; Hanif Mauludin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research is important for tax employees in the public sector, who face high work demands in achieving state revenue targets. Their work engagement can be improved through managing job demands, job resources, and meaningful work, in accordance with the Job Demands-Resources (JD-R) model. By integrating these approaches, this study aims to examine the impact of job demands, job resources, and meaningful work on the work engagement of tax employees in the public sector. In addition, this study also explores the mediating and moderating role of meaningful work in the relationship between job demands, job resources, and work engagement. The research method used is a survey method with a quantitative approach. This research was conducted on 125 employees of the Primary Tax Service Office (KPP) in Malang City, East Java, where the research sample was only devoted to employees at the North and South Malang KPP. Data analysis was carried out using the SEM-PLS method. The results showed that job demands significantly and negatively affect work engagement, while job resources and meaningful work significantly and positively affect work engagement. Among these factors, meaningful work has the strongest influence. In addition, meaningful work mediates the relationship between job demands and job resources with work engagement and moderates the relationship between job demands and work engagement. Based on the results of the study, the practical implication is that the tax office can increase employee engagement by balancing job demands, providing supporting resources, and reinforcing the sense of importance of employee contributions to society.